A Study of Income Tax Policy and Revenue System in India: Assessing the transformation of India's income tax policy and revenue system (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Indian tax system developed to adjust to the public part commanded import substituting industrialisation for just about 45 years after autonomy must be transformed to encourage the changed open economy. This has required reorientation of the tax system from being simply an income instrument which was frequently specific, optional, separated and confiscatory to the one that is income and in the meantime, limits asset mutilations. The issue of transforming the tax system since monetary liberalization was started was intensified by the need to bring incomes up in the short run and improve income efficiency in the medium term to contain vast holding on fiscal shortages and objectives to balance income misfortunes from decreases in import obligations. Tax change in India has borne the local brand. However from numerous points of view, it looks like the best practice approach of widening the base, lessening the rates, decreasing rate separation and keeping the system basic. It has made some amazing progress from the limited based, confounded and confiscatory structure that frustrated the impetuses to the one that is undeniably effective. In spite of flip flounders from year to year, the push and direction of reforms have been to enhance income profitability while limiting twists. The most recent couple of years have likewise observed accentuation on enhancing the tax administration and information system. The change to change over the state level sales tax into a goal based VAT this year is a noteworthy activity.